OPTIMIZATION VIA SIMULATION: SOLUTION CONCEPTS, ALGORITHMS, PARALLELCOMPUTING STRATEGIES AND COMMERCIAL SOFTWARE - Ghiani, Gianpaolo; Legato, Pasquale; Musmanno, Roberto; Vocaturo, Francesca (International Journal of Computing, 2014)
Simulation optimization (or optimization via simulation) is defined as the optimization of performance measures based on outputs from stochastic simulations. Although several articles on this topic have been published, the literature on optimization via simulation is still in its infancy. In this paper the research in this field is reviewed and some issues that have not received attention so far are highlighted. In particular, a survey of solution methodologies is presented, followed by a critical review of parallel computing strategies and commercial software packages. A particular emphasis is put on problems with discrete decision variables.